Rapid identification of Campylobacter species by restriction fragment length polymorphism analysis of a PCR-amplified fragment of the gene coding for 16S rRNA. - Cardarelli-Leite, P (1996)
Restriction fragment length polymorphism analysis of a PCR-amplified DNA fragment of the gene coding for 16S rRNA was performed on 148 previously characterized strains of Campylobacter, Helicobacter, Arcobacter, and Wolinella succinogenes and 13 Campylobacter-like isolates. These strains included clinical, animal, and environmental isolates. PCR amplification generated a 283-bp fragment from all species. The amplicon from each strain was digested with six restriction endonucleases (AccI, AvaI, DdeI, HaeIII, HpaII, XhoI). DdeI was useful for the initial grouping of the strains. Additional discrimination within the different DdeI groups was obtained with AccI, HaeIII, HpaII, and XhoI digestions. The PCR-restriction fragment length polymorphism analysis allowed for the discrimination of members of the genus Campylobacter from members of closely related genera and discrimination between Campylobacter species. The proposed method is simple and rapid and can be useful for the routine identification of Campylobacter-like organisms in clinical or epidemiologic studies.